Actively Seeking Inclusion : Pupils with Special Needs in Mainstream Schools. - Allan, Julie (RoutledgeFalmer, 1999)
Using the accounts of mainstream pupils and pupils with SEN, the text explores the pupils' identities and experiences in relation to each other. It argues that strategies for inclusion have to take into account both mainstream and SEN pupils.